Artificial rubber mineralization by co-cultured bacterial strains - Muralidharan, Manasa; Krishnaswamy, Veenagayathri (International Journal of Biological Research, 2016)
Objective: This study involves the use Natural Rubber degrading Bacterial co-cultures isolated from rubber plantation soil for the degradation of Artificial Rubber.Methods:Plate assay method and liquid assay method by using Mineral Salt Medium was followed for screening of bacteria for its capacity to mineralize Artificial rubber. Degradation was confirmed by Spectrophotometric and Fourier Transform Infra-Red (FTIR) studies. The co-cultures were able to utilize the artificial rubber which was confirmed by Spectrophotometric and FTIR studies.Results: Bacterial cocultures have the capacity to mineralize artificial rubber. Mineralization was observed for 30 days and it was maximum (6.48 x 10-5) on the 20th Day. This was confirmed using SEM and FTIR.Further, these were applied on bioplastics and plastics to study their capacity to degrade them. It was able to degrade them as well which was confirmed using FTIR.Conclusion: From current investigation, it can be concluded that the bacterial cocultures Bacillus cohnii and Brevundimonas naejangsanensis have the capacity to mineralize artificial rubber, plastics and bioplastics. Hence such isolated cocultures can be used in removal of artificial rubber, plastics and bioplastic wastes from the environment.